G-Quadruplex in Gene Encoding Large Subunit of Plant RNA Polymerase II: A Billion-Year-Old Story - Volná, Adriana; Bartas, Martin; Karlický, Václav; Nezval, Jakub; Kundrátová, Kristýna; Pečinka, Petr; Špunda, Vladimír; Červeň, Jiří (International journal of molecular sciences, 2021)
G-quadruplexes have long been perceived as rare and physiologically unimportant nucleic acid structures. However, several studies have revealed their importance in molecular processes, suggesting their possible role in replication and gene expression regulation. Pathways involving G-quadruplexes are intensively studied, especially in the context of human diseases, while their involvement in gene expression regulation in plants remains largely unexplored. Here, we conducted a bioinformatic study and performed a complex circular dichroism measurement to identify a stable G-quadruplex in the gene RPB1, coding for the RNA polymerase II large subunit. We found that this G-quadruplex-forming locus is highly evolutionarily conserved amongst plants sensu lato (Archaeplastida) that share a common ancestor more than one billion years old. Finally, we discussed a new hypothesis regarding G-quadruplexes interacting with UV light in plants to potentially form an additional layer of the regulatory network.
Keywords: rostliny; RNA Polymerase II; molekulární evoluce; ultrafialové záření; výpočetní biologie; fylogeneze; Circular Dichroism; sekvenční seřazení; Rhodophyta; Arabidopsis; sekvence aminokyselin; cirkulární dichroismus; Plants; regulace genové exprese u rostlin; Plant Proteins; nucleic acids; Glaucophyta; evolution; circular dichroism; UV light; G-Quadruplexes; G-kvadruplexy; Computational Biology; RNA-polymerasa II; Sequence Alignment; Gene Expression Regulation, Plant; Phylogeny; rostlinné proteiny; plant science; Amino Acid Sequence; Evolution, Molecular; Ultraviolet Rays